2020
DOI: 10.1109/access.2020.3025357
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Control of Truck Cabins With the Adaptive Vectorial Backstepping Design of Electromagnetic Active Suspension System

Abstract: The active suspension system is an important equipment that isolates the vibrations that may come from outside in a land vehicle. In heavy vehicles, the active suspension system can be used to dampen vibrations in the driver's cabin. The electromagnetic actuator is used as an active element in suspension system. Traditionally, the use of active suspension systems is mainly on automobiles and the studies related to heavy vehicles like trucks lack enough interest. In this study, dynamic modeling of a three-axle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 70 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…Finally, the results showed that the proposed approach gave an improvement in ride comfort. Basaran [28] proposed an electromagnetic active suspension system for a three-axle truck cabin. The purpose of their work is to reduce vibration transmitted from road unevenness by using electromagnetic actuators.…”
Section: Kim and Leementioning
confidence: 99%
“…Finally, the results showed that the proposed approach gave an improvement in ride comfort. Basaran [28] proposed an electromagnetic active suspension system for a three-axle truck cabin. The purpose of their work is to reduce vibration transmitted from road unevenness by using electromagnetic actuators.…”
Section: Kim and Leementioning
confidence: 99%
“…In addition, an active suspension system is also proposed to compensate for the vibration. The previous studies propose PID (Proportional–Integral–Differential controller) designed based on the dynamic model (Wang et al, 2018) and the adaptive control method (Basaran et al, 2020) for the active suspension system. Although these methods effectively compensate for vibration, implementing additional parts for the suspension system increases the cost.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the active suspension system is also widely discussed due to its impact on the safety and comfort of driving, especially in heavy vehicles. Basaran [13] developed an analytical model of the active suspension system of a truck cabin. The system is controlled by an electromagnetic actuator, which, compared to a pneumatic system, is precise and operates with lower inertia.…”
Section: Introductionmentioning
confidence: 99%